Integration of microfluidic chip with biomimetic hydrogel for 3D controlling and monitoring of cell alignment and migration. Issue 4 (6th August 2013) - Lee, Kwang Ho; Lee, Ki Hwa; Lee, Jeonghoon; Choi, Hyuk; Lee, Donghee; Park, Yongdoo; Lee, Sang‐Hoon
Abstract A biomimetic hydrogel was integrated into microfluidic chips to monitor glioma cell alignment and migration. The extracellular matrix‐based biomimetic hydrogel was remodeled by matrix metalloprotease (MMP) secreted by glioma cells and the hydrogel could thus be used to assess cellular behavior. Both static and dynamic cell growth conditions (flow rate of 0.1 mL/h) were used. Cell culture medium with and without vascular endothelial growth factor (VEGF), insensitive VEGF and tissue inhibitor of metalloproteinases (TIMP) were employed to monitor cell behavior. A concentration gradient formed in the hydrogel resulted in differences in cell behavior. Glioma cell viability in the microchannel was 75–85%. Cells in the VEGF‐loaded microchannels spread extensively, degrading the MMP‐sensitive hydrogel, and achieved cell sizes almost fivefold larger than seen in the control medium. Our integrated system can be used as a model for the study of cellular behavior in a controlled microenvironment generated by fluidic conditions in a biomimetic matrix. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1164–1172, 2014.